The Garden Of Education of the Qur'an As a Tool for the Formation of the Religious Character of the Children in the Midst of the Congregation - Nindia Oktiviana; Nurul Hidayah; M Hamzah Harianto; Rifky Dzikrillah (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
Al-Qur'an Education Park (TPQ) is a means to educate and build children's character, because it is through this Al-Qur'an Education Park (TPQ) that children are trained from an early age to know how to know, understand, learn, and apply Islamic education as a guide to life in the child's self and religious character in the future, because in this modern era the application of Islamic education is needed as a form of character with a religious spirit. Sedayu Sub-District is one of the sub-districts in Turen sub-district which established and implemented Islamic education through the Al-Qur'an Education Park. In an effort to be able to build the character of children who have Islamic personality from an early age, Sedayu Village continues to develop and implement Islamic education, namely through the Al-Qur'an Education Park (TPQ) Al-Ichsan. Through TPQ Al-Ichsan education in the Sedayu Village, it is hoped that it will be able to cultivate the character of children from an early age who adhere to Islamic religious values. Basically, Al-Qur'an Education Park (TPQ) plays an important role in improving the quality of Islamic education in society. So as to be able to build a young generation who has good morals and an Islamic spirit in this modern era.